IMPAIRMENT OF AN ENDOTHELIAL NAD+-H2S SIGNALING NETWORK IS A REVERSIBLE CAUSE OF VASCULAR AGING. (11th November 2018) - Bonkowski, M S; Das, A; Schultz, M B; Lu, Y; Mitchell, J; Wu, L; Guarente, L; Sinclair, D A
Abstract: With aging there is a notable decline in capillary density and blood flow contributing to mortality and morbidity. The use of NAD+ boosters to reverse aspects of aging, is in part, through the mechanism of activating sirtuin deacylases (SIRT1–SIRT7) that mediate the benefits of exercise and calorie restriction (CR). We show here that SIRT1 in endothelial cells is a key mediator of pro-angiogenic signals secreted from myocytes. Treatment of mice with the NAD+ precursor nicotinamide mononucleotide (NMN) improves blood flow and increases endurance in advanced aged mice by promoting SIRT1-dependent increases in capillary density, an effect augmented by exercise or increasing the levels of hydrogen sulfide (H2S), a CR mimetic and regulator of endothelial NAD+ levels. These findings have implications for improving blood flow to organs and tissues, increasing performance, and reestablishing a virtuous cycle of mobility in aged individuals.